Mapping Television ownership concentration in West Java after the Analog Switch-Off - Harikal Ramadhan, Muhamad; Rahmat Hidayat, Dadang; Yudhapramesti, Pandan (Universitas Ahmad Dahlan, 2025)
Broadcasting digitization in Indonesia reached a major turning poin with the implementation of the Analog Switch-Off (ASO), as mandated by the Job Creation Law No. 11 of 2020. This policy requires television stations to migrate from analog to digital broadcasting, which brings significant changes to technological advancements and the broadcasting business ecosystem, especially in the media ownership structure. Prior to the ASO, television ownership in West Java was highly centralized and dominated by a few large media groups, which impacted the diversity of content production and distribution. This study aims to analyze the impact of the ASO on the concentration of television ownership in West Java and see whether this transition encourages media diversity or strengthens media conglomeration. Using a qualitative approach with descriptive case study method, this research utilizes Anthony Giddens' Structuration Theory to explore the relationship between media ownership structure and agency in the post-ASO era. Data was collected through in-depth interviews with representatives from television stations and industry stakeholders, supported by document analysis. The findings reveal that despite regulatory changes, media ownership remains concentrated among large networks, limiting opportunities for independent and local television stations to thrive. The study highlights that structural barrier, including financial constraints and regulatory complexity, hinder the democratization of media ownership. In conclusion, while ASO provides the potential for a more diverse broadcasting landscape, existing power structures still dominate, necessitating further policy interventions to promote fair competition and ownership diversity in Indonesia's digital broadcasting era.